Does environmental knowledge predict attitudes and behaviors in environmental literacy? Evidence from senior high school students - Raditha Putri Cahyani; Adi Rahmat; Yanti Hamdiyati; A. Amprasto; Muhamad Wafda Jamil (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The development of science and technology without individual environmental awareness has led to a decline in environmental quality. This issue can be addressed by enhancing environmental literacy, which includes ecological knowledge, cognitive skills, environmental attitudes, and behaviors. In practice, the question arises as to whether knowledge influences environmental attitude and behavior or vice versa. A study was conducted with 11th-grade students (n = 26) in Cimahi to investigate the role of environmental literacy in shaping attitudes and behaviors toward the environment. Results indicated that 58% of students had a moderate level of environmental literacy, primarily due to low scores in ecological knowledge (M = 36.15) and cognitive skills (M = 44.68), despite positive environmental attitudes (M = 81.67) and behaviors (M = 73.46). Correlation analysis showed no significant relationship between knowledge and environmental attitudes or behaviors (r = 0.18; p = 0.38). The formation of these attitudes and behaviors is influenced not only by cognitive learning but also by external factors, such as family habits and school culture. Multiple linear regression analysis suggested that ecological knowledge (β = 0.456) and cognitive skills (β = 0.425) significantly contribute to environmental literacy, more so than attitudes (β = 0.248) and behaviors (β = 0.335). It is essential to develop educational programs that effectively balance students' cognitive and affective aspects in environmental learning to build strong environmental literacy skills.